Implementasi Solar Cell Panel Untuk Penerangan Umum Di Wilayah Serang Baru - Bekasi - Ibnu Hajar; Yuliansyah Yuliansyah; Jumiati Jumiati; Dhami Johar Damiri; Martin Choirul Fatah; I Made Indradjaja Marcus Brunner (Unri Conference Series: Community Engagement, 2021)
Community Service (PkM) partner are located in Kp. Cipalahlar RT. 010/005 Sukaragam Village, Serang Baru District, Bekasi Regency, Jawa Barat Province. The Kp. Cipalahlar, although.it is surrounded by a residential area and not far from an industrial area in Bekasi, this village has received less attention from the Bekasi Regency Government, it can be seen the electrical cable network that is connected to the houses of the villagers is only put on trees and no electricity poles at all. So, it can be understood when in Kp. Cipalahlar does not have public street lighting facility (PJU) so when night comes the village becomes very dark. Therefore, to help residents get lighting at night, especially lighting on concrete roads, the community service (PkM0 team installed three public street lighting (PJU). The PJU is very useful for residents to carry out their activities at night such as going to the mosque for congregational prayers. The mosque will be lively with the presence of children to recite the Qur’an. The type of PJU installed is PJU based on solar cell panels because it is more practical and requires almost no maintenance in operation and has a long service life, up to 25-30 years.